Evaluation of E-Learning Approaches Using AHPTOPSIS Technique - Mohammed, Husam Jasim; Mat Kasim, Maznah; Mohd Shaharanee, Izwan Nizal (Universiti Teknikal Malaysia Melaka, 2018)
Strategic preparation of e-learning application includes decision making regarding the most suitable type of elearning on different levels. The survey has been carried out on the sample of 95 respondents consisted of administrative and academic staff, and postgraduate students in Malaysia.They were asked to assess the relative importance of five e-learning evaluation criteria to be analysed by using AHP technique.Furthermore, they also rated the performance of five identified e-learning approaches under each of the requirements.The overall performance of each e-learning approach was computed by using TOPSIS method.The results suggested that Flipped Classroom is the most suitable e-learning approach, while ‘Strategic readiness for e-learning implementation’ found to be the most important criterion.The paper is suggesting a quantitative evaluation method for decision-makers who are strategising modern technologies in higher educational settings.